Hygiene and Sanitation of Refill Drinking Water Depots in Relation Escherichia coli: A Quantitative Study - Abas, Muhamad; Irawan, Angki; Marpaung, Dorkas (Gema Lingkungan Kesehatan, 2025)
Clean water is essential for various daily needs such as drinking, cooking, bathing, and washing. Ensuring proper hygiene and sanitation is critical to prevent waterborne diseases, particularly those caused by Escherichia coli. This descriptive observational study conducted from March to June 2024. The aim of this research is to worker hygiene practices and sanitation conditions at Refill Drinking Water Depots (RDWDs) as well as their relation to the presence of E. coli in the Timika Jaya Health Center area, Mimika Regency. All 20 certified RDWDs in the area were included in this study, involving workers and managers as respondents. Data were collected through sanitation inspections and water sampling for laboratory testing, and analyzed using SPSS to determine frequency distributions and percentages. The majority of respondents were male (87.1%), aged 25–30 years (38.7%), had completed senior high school (54.8%), and worked ≥8 hours per day (100%). In terms of hygiene compliance, only 3.2% of workers met the required standards, while 96.8% did not. All depots (100%) met sanitation standards related to location and equipment. However, 6 depots (30%) were found to be contaminated with E. coli. These findings indicate that inadequate personal hygiene among workers is a key risk factor for E. coli contamination, despite compliance with infrastructural sanitation standards. Regular monitoring, hygiene training, and enforcement of health regulations are strongly recommended to ensure the safe distribution of drinking water.